Diversity and novelty in environmental enrichment increases enrichment use in juvenile American mink (Neogale vison) - Clark, Gabrielle B.; Díez-León, María; Meagher, Rebecca K. (Frontiers in Animal Science, 2023)
It is standard practice on mink farms in Canada to provide one manipulable environmental enrichment (EE) in each cage to benefit animal health and welfare, and once an enrichment is introduced, it must remain in the cage for the duration of that animal’s life. However, mink might habituate to permanently present enrichments, which reduces interaction with these items over time. In this study, juvenile mink were provided with multiple EEs (mobile and hanging items) that were regularly exchanged to maintain novelty in addition to a standard, permanently present EE (enriched kits; EK). EE use over time, as well as interactions based on EE type, were compared to that of two groups which were standard-housed as juveniles (control; C and enriched at whelping; EW) with access to a permanently available standard enrichment. EK housing was found to significantly increase kits’ EE use compared to standard housing (p < 0.001). Despite some evidence of rapid habituation to novel objects (e.g., decreased use of hanging rope EE in second week of access: p = 0.019), item exchange appeared to have a sustaining effect on exploration of all EEs in the cage, including familiar objects. Thus, it may be beneficial to provide farmed mink with multiple EEs, both novel and familiar, to promote their optimal use and facilitate welfare benefits. Objects with greater manipulability or malleability were also used more by kits than those with fewer possible uses (e.g., pig’s ear versus other, less malleable mobile EEs: p < 0.001; rope versus less malleable hanging EE: p < 0.001). Although this effect was persistent across all periods of observation, it is possible that kit age at time of object introduction or differences in novelty may have contributed to these differences in their use. Further research is required to determine kits’ preference for different EE types when all items are equivalently novel, and when differences in developmental stage are fully accounted for.